Minimally invasive mitral valve annuloplasty confers a long-term survival benefit compared with state-of-the-art treatment in heart failure with functional mitral regurgitation. (1st October 2017) - Penicka, Martin; Kotrc, Martin; Ondrus, Tomas; Mo, Yujing; Casselman, Filip; Vanderheyden, Marc; Van Camp, Guy; Van Praet, Frank; Bartunek, Jozef
Abstract: Background: Clinical impact of the minimally invasive surgical mitral valve annuloplasty (MVA) of functional mitral regurgitation (FMR) in systolic heart failure on top of the state-of-the-art standards of care remains controversial. Therefore, we aimed to compare clinical outcomes of isolated MVA using the mini-invasive videothoracoscopic approach versus the state-of-the-art (CON = conservative) treatment in patients with chronic systolic heart failure and symptomatic FMR. Methods: The study population consisted of 379 patients (age 68.9 ± 11.0 years, 62.8% males) with left ventricular (LV) systolic dysfunction, symptomatic FMR and previous heart failure hospitalization. A total of 167 patients underwent undersized MVA and 212 patients were treated conservatively. A concomitant MAZE was performed in 53 (31.7%) patients. Results: In the MVA group, the periprocedural and the 30-day mortality were 1.2% and 4.8%, respectively. During the median follow-up of 7.1 years (IQR 3.5–9.8 years) a total of 74 (44.3%) and 138 (65.1%) died in the MVA and the CON group, respectively ( p < 0.001). The lowest mortality was observed in MVA combined with MAZE (22.6%; p < 0.01). In Cox regression analysis, age, MVA with MAZE emerged as independent predictors of both all-cause mortality and rehospitalizations for heart failure (all p < 0.05). MVA was associated with significantly greater symptomatic improvement and reduction of FMR than the conservative treatment (both p < 0.001). Reverse LV remodeling was observed only in the MVA combined with MAZE group ( p < 0.01). Conclusions: In patients with symptomatic FMR, minimally invasive MVA, in particular in combination with MAZE, confers an independent long-term survival benefit compared with the state-of-the-art treatment.